The Effect of Competence and Motivation through Work Discipline on Employee Performance - Mulyeni, Sri; Yulistianti, Putri (Universitas Mercu Buana, 2025)
This study aims to determine and explain the effects of competence, work motivation through work discipline on employee performance at PT. Pou Yuen Indonesia. Respondents taken as many as 91 employees, data analysis was carried out quantitatively with data collection techniques through questionnaires and the analysis used was phat analysis, the results of the study showed that competence had a positive impact on employee performance at PT. Pou Yuen Indonesia. Work motivation has a positive effect on employee performance. Competence through work discipline has a positive impact on employee performance. Work motivation through work discipline has a positive effect on employee performance. The results of the coefficient of determination of the R2 value are very good, so it can be concluded that competence, work motivation, work discipline have a positive impact on employee performance